Effectiveness, safety, and economic evaluation of adjuvant moxibustion therapy for aromatase inhibitor-induced arthralgia of postmenopausal breast cancer stage I to III patients: Study protocol for a prospective, randomized, assessor-blind, usual-care controlled, parallel-group, pilot clinical trial. Issue 38 (September 2019) - Shin, Seungwon; Jang, Bo-Hyoung; Park, Seung-Hyeok; Lee, Jin-Wook; Chae, Min Soo; Kim, Namhoon; Suh, Hae Sun; Han, Sola; Min, Sun Young; Baek, Sun Kyung; Lim, Yu Jin; Hwang, Deok-Sang
Abstract: Introduction: This study is a prospective, assessor-blinded, parallel-group, randomized controlled pilot trial to explore the effectiveness of 12-week adjuvant moxibustion therapy for arthralgia in menopausal females at stage I to III breast cancer on aromatase inhibitor (AI) administration, compared with those receiving usual care. Methods/design: Forty-six menopausal female patients with breast cancer who completed cancer therapy will be randomly allocated to either adjuvant moxibustion or usual care groups with a 1:1 allocation ratio. The intervention group will undergo 24 sessions of adjuvant moxibustion therapy with usual care for 12 weeks, whereas the control group will receive only usual care during the same period. The usual care consists of acetaminophen administration on demand and self-directed exercise education to manage AI-related joint pain. The primary outcome is the mean change of the worst pain level according to the Brief Pain Inventory—Short Form between the initial visit and the endpoint. The mean changes in depression, fatigue, and quality of life will also be compared between groups. Safety and pharmacoeconomic evaluations will also be included. Discussion: Continuous variables will be compared by an independent t test or Wilcoxon rank-sum test between the adjuvant moxibustion and usual care groups. Adverse events will be analyzed using the chi-square or Fisher exact test. The statistical analysis will be performed by a 2-tailed test at a significance level of .05.